Reading Southern History : Essays on Interpreters and Interpretations - Feldman, Glenn (Book collections on Project MUSE., 2001)
This collection of essays examines the contributions of some of the most notable interpreters of southern history and culture, furthering our understanding of the best historical work produced on the region. Historian Glenn Feldman gathers together a group of essays that examine the efforts of important scholars to discuss and define the South's distinctiveness. The volume includes 18 chapters on such notable historians as John Hope Franklin, Anne Firor Scott, Frank L. Owsley, W.J. Cash, and C. Vann Woodward, written by 19 different researchers, both senior hi.